Results of the flipped curriculum resources assessment for additional subject preparation of school children - Barkhatova, Daria; Lomasko, Pavel; Simonova, Anna (AIP conference proceedings, 2024)
The paper presents the results of the succeeding stage of a research project aimed at improving the methods and means of organizing additional subject training for schoolchildren in a remote mode. The relevance of this area of scientific and methodological activity is determined by the needs of modern school education, which is in conditions of intensive digital transformation. The main purpose of this publication is to test theoretically the methodology for assessing the developed “flipped” scientific resources and discuss the results obtained. The main materials and methods of the study are theoretical and methodological analysis of scientific and methodological sources and a comprehensive examination of sets of "inverted" educational resources in mathematics, physics and computer science developed by students of the Krasnoyarsk State Pedagogical University named after V.P. Astafiev. Pedagogical workers of schools and organizations of additional education for children in Krasnoyarsk acted as experts. The evaluation was carried out during August and early September 2022 by familiarizing the experts with online resources and then completing the online form. The paper describes and analyses the results obtained during the examination, methods for calculating aggregated and integration values. The final part of the paper contains information on the further application of the obtained data for the improvement and subsequent testing of the own regional tool environment developed by the authors in the form of a web application that allows creating "flipped" learning resources based on a topological question-task knowledge tree in the form of an online constructor.